Herbal combination 'HAGE-101912' Ameliorates gastroesophageal reflux disease in rats - Mohammed M Azeemuddin; Madan M Narendra; Onkaramurthy Mallappa; Suryakanth D Anturlikar; Mirza R Baig; Mohamed Rafiq (Wolters Kluwer Medknow Publications, 2023)
Background: Gastroesophageal reflux disease (GERD) is a chronic, relapsing disorder. In this era of modern and fast-track lifestyle and food habits, the incidence of GERD is rapidly increasing. Currently, proton pump inhibitors (PPIs) are the primary choice of treatment. However, the associated side effects and a high relapse rate give rise to the need to explore alternative therapies. Objective: The study aimed to evaluate HAGE-101912, an herbal combination, in different experimental models of GERD. Methods: Antacid activity was assessed based on H+/K+ATPase inhibitory activity of parietal cells using artificial gastric juice. Tonic contraction of the lower esophageal sphincter (LES) was evaluated using an AD Instrument. A GERD model of the pylorus and fundus ligation (preventive and curative models) in rats was selected to assess the efficacy of HAGE-101912 at a dose of 250 mg/kg body weight, and various parameters such as the gastric pH, gastric volume, total acidity, gross esophageal ulcer index, and histopathological changes were evaluated. The prokinetic activity was assessed using the phenol red method. Results: HAGE-101912 increased the acid-neutralizing capacity (P < 0.001), decreased H+/K+ATPase activity (P < 0.01), and increased the contraction of the LES. In the preventive model, HAGE-101912 significantly reduced the gastric acid volume (P < 0.01), total acidity (P < 0.001), and gross esophageal ulcer index (P < 0.01); increased the gastric acid pH (P < 0.01); and protected the esophageal epithelium. In addition, HAGE-101912 increased gastric emptying and gastrointestinal transit through its prokinetic activity (P < 0.05). Conclusion: HAGE-101912 has a beneficial effect in GERD as it effectively inhibits the H+/K+ATPase, increases the gastric pH, restores the LES function, protects the esophageal epithelium, and increases gastric emptying and transit.